Structural safety and usability evaluation of one way voided slab with Formwork - Moowon Hur; Hyun-Ho Lee; Taewon Park (Journal of Asian Architecture and Building Engineering, 2025)
This study proposed a formwork-integrated hollow slab with an improved shape made of a hollow material. The performance of the proposed formwork-integrated hollow slab was evaluated through flexural and shear tests. The results of the VPS flexural performance test showed that, for both FPS-01-1 and FPS-01-2, the yield load value was approximately 94 to 101% compared to that of FPS-00, with an average value of 97.5%. FNS-01-1 and FNS-01-2 showed about 99.4% of the yield load of the FNS-00 specimen, while FNS-02-1 and FNS-02-2 showed approximately 95.2% of the flexural performance of the FNS-00 specimen. As a result of the shear performance test of the integrated formwork hollow slab, in the case of SPS-01, the yield load value was about 92.4% compared to that of SS-00, which was slightly less than that of SS-00. This is believed to be due to the fact that the concrete cross-section is missing when using the hollow material. Also, this study also evaluated the proposed slab’s safety against immediate deflection and long-term deflection. After measuring long-term deflection for three months, the deflection value presented in the ACI 318–19 standard was found to be satisfied. This is because the hydration of concrete was stabilizing to some extent, and the causes of deflection were changing from external load factors to deflection due to drying shrinkage and creep acting inside the concrete